Domestic microwave oven adapted for fast heat treatment of Ba0.5Sr0.5(Ti0.8Sn0.2)O-3 powders - Keyson, D.; Volanti, D. P.; Cavalcante, L. S.; Simoes, A. Z.; Souza, I. A.; Vasconcelos, J. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2007)
In this work, BSTSn powders prepared by the polymeric precursor method were heat treated in a domestic microwave oven (MW) using a SiC susceptor to absorb the microwave energy and transfer the heat to the powder. The main advantage of MW is to reduce the thermal treatment time for phase crystallization. The powders were heat treated at 300 degrees C for 20 h in conventional oven, 300 degrees C for 10 min, 20 min, and 30 min in MW and at 500 degrees C for 1 min in MW. After thermal treatment, the photoluminescent properties of powders at room temperature were analyzed. (c) 2007 Published by Elsevier B.V.
Keywords: microwave processing; fast heat treatment; BSTSn; photoluminescence